2016
DOI: 10.1371/journal.pone.0150187
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Oceanic Migration of Silver Japanese Eels

Abstract: The oceanic migration of silver Japanese eels starts from their continental growth habitats in East Asia and ends at the spawning area near the West Mariana Ridge seamount chain. However, the actual migration routes remain unknown. In this study, we examined the possible oceanic migration routes and strategies of silver Japanese eels using a particle tracking method in which virtual eels (v-eels) were programmed to move vertically and horizontally in an ocean circulation model (Japan Coastal Ocean Predictabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…They subsequently penetrate continental waters, turning into pigmented yellow eels, where they colonize a large range of continental habitats from brackish to freshwater (Arai & Chino, ; Daverat et al., ). After a growth phase lasting from 3 to over 30 years, yellow eels metamorphose into silver eels and migrate back to their spawning grounds (Béguer‐Pon, Castonguay, Shan, Benchetrit, & Dodson, ; Chang, Miyazawa, & Béguer‐Pon, ; Righton et al., ). The eels mature en route and presumably die following spawning.…”
Section: Introductionmentioning
confidence: 99%
“…They subsequently penetrate continental waters, turning into pigmented yellow eels, where they colonize a large range of continental habitats from brackish to freshwater (Arai & Chino, ; Daverat et al., ). After a growth phase lasting from 3 to over 30 years, yellow eels metamorphose into silver eels and migrate back to their spawning grounds (Béguer‐Pon, Castonguay, Shan, Benchetrit, & Dodson, ; Chang, Miyazawa, & Béguer‐Pon, ; Righton et al., ). The eels mature en route and presumably die following spawning.…”
Section: Introductionmentioning
confidence: 99%
“…Although Manabe et al (2011) tracked "silver eel" stage A. japonica individuals released near Japan using pop-up tags, the eels neither reached the spawning area nor showed evidence of spawning related behaviors. A modelling simulation study by Chang et al (2016) suggested that ocean circulation significantly affected the spawning migration route and duration of Japanese eels after their departure from the south coast of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The migration process of Japanese eels, however, is not well understood due to limited direct observational evidence on adult migration 23 or larval dispersal 24 . Numerical modelling methods, therefore, have been used to simulate the potential migration paths of Japanese eels, and to evaluate their linkages to ocean-atmosphere changes 12 , 14 , 15 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%